Ab Initio Molecular–Dynamics Study of Structural and Bonding Properties of Liquid Fe–Light–Element–O Systems Under High Pressure - Ohmura, Satoshi; Shimojo, Fuyuki; Tsuchiya, Taku (Frontiers in Earth Science, 2022)
The structural and bonding properties of liquid iron-light-element-oxygen ternary systems such as Fe–H–O, Fe–C–O, Fe–Si–O, and Fe–S–O under high pressure are studied by ab initio molecular dynamics simulations. H, C, O, Si, and S are the candidate light elements in the Earth’s outer core (liquid iron is a major constituent). From our simulations, it is found that H, C, and O show “interstitial” type behavior while Si and S show “substitutional” type behavior in the liquid iron-light-element-O ternary systems. For the interactions between light elements, C–C, Si–Si, and Si–O show covalent-like interactions even under high-pressure condition. The Si–O covalent bond causes a shift in the ionic charge of Si to more positive, which could be related to the immiscibility of liquid Fe–Si–O.